Pengaruh Pengendalian Mutu, Inovasi, dan Sumber Daya Manusia terhadap Kinerja Karyawan pada PT Mitra Industrial Chrome Teknologi Tanggerang - Rudy Habibie Zulkarnain; Kardinah Indrianna Meutia; Nita Komala Dewi (STIKes Ibnu Sina Ajibarang, 2024)
This research intends to examine how the problem of Employee Performance of PT Mitra Industrial Chrome Technology Tanggerang. On this occasion the researcher get information about how problems in employee performance in form of initial interviews with several employees who work at PT Mitra Industrial Chrome Technology. Industrial Chrome Technology. Based on the results of initial interviews with several employees who work at PT Mitra Industrial Chrome Teknologi Tanggerang that there are production employees who make mistakes in making parts.